ANALISIS KEMAMPUAN MEMBACA SISWA KELAS 1 DENGAN MENGGUNAKAN MEDIA FLASHCARD DI SDN 2 BUMI NABUNG UTARA - Khoiriyah, Miftakhul; Aris, Ika Evitasari; Rahayu, Maulina (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to analyze the early reading skills of first-grade students at SDN 2 Bumi Nabung Utara through the use of flashcard media. The research background is grounded in the importance of reading as a fundamental skill in elementary education. Employing a qualitative descriptive approach, the subjects included students, classroom teachers, and relevant learning documents. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the reading process occurs gradually, starting from letter recognition to reading simple sentences. Students demonstrated varied abilities in recognizing letters, pronouncing sounds, and understanding the meaning of words or sentences. Their responses to flashcard use were positive, reflected in attention, interest, and active participation. Overall, flashcards effectively supported teacher–student interaction in early reading, providing a clear depiction of the actual condition of beginning literacy skills in elementary school.